Letter from Norman Nicholson to Jane Tolmach - Norman Nicholson:::::: (1973)
A letter from Norman Nicholson, the Vice President of The Talley Corporation, requesting that Jane Tolmach discuss the matter of the Fairchild Republic Company A-10 Close Support Fighter.